514 CANCER CELLS PERSIST AFTER COMPLETE PATHOLOGICAL RESPONSE IN ESOPHAGEAL ADENOCARCINOMA. (14th September 2020) - Walker, R; Harrington, J; Grace, B; Sharpe, B; Breininger, S; Izadi, F; Kelly, J; Byrne, J; Noble, F; Rose-Zerilli, M; Underwood, T
Abstract: : In esophageal adenocarcinoma (EAC) with apparent pathological complete response (pCR) to neoadjuvant therapy (NAT) debate remains as to whether esophagectomy is required. Recurrence after pCR is not limited to distant metastases outside radiation or resection fields. It is unknown if cancer persists below the lower detection limit of current diagnostic technology. Trials randomising patients with apparent pCR to esophagectomy or active surveillance are currently recruiting in an attempt to spare patients the morbidity of esophagectomy. Methods: Single cell (scRNAseq) was performed on fresh tissue taken at surgical resection to determine the transcriptomic profiles of cell populations in 24 EAC tumours and matched normal samples. Five tumour-normal pairs were also analysed using bulk RNA sequencing and high-precision mass spectrometry proteomics. Immunohistochemistry (IHC) was used to confirm pCR. Paired scRNAseq analysis of pre-and post-treatment specimens from three patients was used to compare transcriptomic profiles before and after NAT. Cancer cells were assigned a cancer stem cell module score curated from published gene sets. Results: We analysed a total of 22, 738 single cells forming 29 different cell states. In two samples with pCR, we repeated the pathological analysis and performed IHC using antibodies to known cancer proteins and identified no residual cancer cells (figure 1A). Bulk tissue RNA (figure 1B) and proteomic analysis did not detect cancer genes or proteins in the pCR samples. ScRNAseq, conversely, revealed small populations of persistent cancer cells in both complete responders (12/978 and 45/774) (figure 1C). Transcriptomic analysis of these residual cells identified upregulation of stem cell markers and high cancer stem cell scores in these remaining cells (figure 1D). Conclusion: We have determined the cell states present across multiple different EAC and normal esophageal samples. We have shown cancer cells persisting after NAT, in patients with apparent pCR, beneath the lower detection limit of standard diagnostic approaches. These cells express gene programs consistent with cancer stem cells. Cancer stem cells are a critical subpopulation that drive tumour initiation, growth, and resistance to therapy. Esophagus sparing approaches in pCR may subject patients to risk of progression.